The FiberTAG project: Tagging dietary fibre intake by measuring biomarkers related to the gut microbiota and their interest for health. Issue 1 (5th February 2020) - Neyrinck, A. M.; Rodriguez, J.; Vinoy, S.; Maquet, V.; Walter, J.; Bischoff, S. C.; Laville, M.; Delzenne, N. M.
Abstract: The scientific rationale for dietary fibre intake recommendations comes from the recognition of their benefits for health based on studies first published many years ago. It remains unclear which are the key physiological effects generated by dietary fibre in view of the diversity of the food components considered as dietary fibre, of the relevance of their classification (soluble and insoluble) and from the recent discoveries putting forward their interactions with the gut microbiota. The project FiberTAG ( Joint Programming Initiative 'A Healthy Diet for a Healthy Life' 2017–2020 www.fibertag.eu/ ) aims to establish a set of biomarkers (markers of gut barrier function and bacterial co‐metabolites including volatile compounds and lipid derivatives), measured in different biological compartments (faeces, blood or breath) linking dietary fibre intake and gut microbiota‐related health effects. The FiberTAG consortium brings together academic and industrial partners from Belgium, France, Germany and Canada to share data and samples obtained from existing as well as new intervention studies in order to evaluate the relevance of such biomarkers. The FiberTAG consortium is currently working on five existing cohorts (prospective observational or nutritional interventions in healthy or obese patients), and a number of new intervention studies to analyse the effect of insoluble dietary fibre (wheat bran and chitin‐glucan, provided by the industrial partners) in healthy individuals or in obese patients at high cardiometabolic risk.